Building a Hand and Upper Extremity Transplantation Program: Lessons Learned From the First 20 Years of Vascularized Composite Allotransplantation. (March 2020) - Mendenhall, Shaun D.; Brown, Stav; Ben-Amotz, Oded; Neumeister, Michael W.; Levin, L. Scott
Background: Upper extremity transplantation is a quality-of-life enhancing treatment for select patients with upper extremity loss. This article reviews the preoperative, intraoperative, and postoperative challenges in the upper extremity transplantation process and the lessons learned from the first 2 decades of hand transplantation.Methods: Key components of the author's hand transplantation protocol including patient selection, donor screening, surgical rehearsal, donor procurement, transplantation, immunosuppression, and patient outcome reporting/follow-up are reported to assist other teams who wish to establish a hand transplantation program.Results: There have been many advancements in the first 20 years of hand transplantation including better patient selection criteria, the recent addition of pediatric patients, improved surgical techniques such as the use of virtual surgical planning, and improved immunosuppression protocols. Improvement has also taken place in the tracking and reporting of hand transplant outcomes, but more work is clearly needed to fully define the benefits of transplantation, especially for pediatric patients.Conclusions: Over the past 20 years, significant progress has been made in upper extremity transplantation although a number of challenges remain including how to best document and share outcome measures, optimize immunosuppression, and diagnose/treat rejection. The authors encourage upper extremity transplant programs to report their experience and protocols to advance hand transplantation as standard of care for properly selected individuals.